Brief report: Contemplate your symptoms and re-evaluate your health. A study on working adults. (September 2019) - Andreasson, Anna; Schiller, Helena; Åkerstedt, Torbjörn; Berntson, Erik; Kecklund, Göran; Lekander, Mats
We investigated whether self-ratings of health are affected by a symptom rating. A diary including a one-item self-rating of health ("pre–self-rated health"; 1 = excellent, 7 = very poor), a subsequent 26-item rating of symptoms, and thereafter a second (identical) health rating ("post–self-rated health") was completed by 820 persons 21 times. Self-rated health worsened significantly ( p < .0001) after the symptom rating, from 2.72 pre–self-rated health (95% confidence interval: 2.70–2.74) to 2.77 post–self-rated health (95% confidence interval: 2.75–2.79) and more so in persons who reported more symptoms ( b = .058, p < .05). The results support the notion that subjective health perception is influenced by attending to symptoms, especially so in persons with a high symptom burden.